SURVEI MOTIVASI MASYARAKAT UNTUK BEROLAHRAGA PADA SUASANA COVID 19 (CORONA) DI TAMAN OLAHRAGA DAN REKREASI KULINER RUMBAI (TORR) PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The rapid spread of the covid-19 pandemic has caused people to inevitably have to struggle with this situation. The government implements social distancing provisions so that more people stay at home. Since the COVID-19 pandemic, every community who will do sports must be able to do it in their own home environment or in public places with the obligation to follow health protocols. Rumbai District has a Rumbai Culinary Sports and Recreation Park (TORR) Pekanbaru where this park has many facilities and facilities such as the availability of sports fields, namely soccer fields and basketball fields, there are also bicycle rental services, children's toys, and even badminton rental with the availability of these facilities can motivate people to carry out movement activities with supports from intrinsic and extrinsic factors, because with the occurrence of the covid-19 pandemic, people are asked to be more creative in maintaining their physical fitness, and it will make it easier for people to continue to live healthy lives. This research uses descriptive research method. The population in this study were people who visited the Rumbai Culinary Sports and Recreation Park (TORR) Pekanbaru, the sampling technique in this study was a random sampling technique by taking a random sample of 35 people. The instrument used to collect data is a questionnaire. The data analysis technique used is to calculate the questionnaire scores on each exercise motivation indicator. Based on the results of this researh, it is known that the results of the survey on people's motivation to exercise in an atmosphere of covid 19 (corona) at the Rumbai Culinary Sports and Recreation Park (TORR) Pekanbaru showed that the average value of the percentage score of the questionnaire score of the two indicators was 59.63% which was classified as in the sufficient category because it is located in the 41%-60% intervalKey Words: Community Motivation to Exercise at TORR